Lactate Dehydrogenase and Blast Rates in the Diagnostic Phase and the Late Remission Phase of Acute Childhood Leukaemia Patients - Rosdiana, Nelly; Kemal , Novia (CoinReads Media Prima, 2024)
Introduction: Leukaemia is a blood cell malignancy that manifests as young cells in the peripheral blood. In developing countries, ALL account for 80% of leukemia cases. Despite the implementation of contemporary intensive therapy, remission is attained in 98% of patients. LDH have found to have benefit in diagnosing and may be prognostic factor especially in predicting remission in ALL. Methods: This observational cohort study took place at the pediatric ward of RSUP H. Adam Malik – Medan, from August 2022 to February 2023. Subjects meeting the study criteria were assessed to know the relationship between LDH between the initial phase and remission phase of ALL. Multivariate logistic regression analysis was then conducted for the combined scores. Results: We found significant differences in LDH and blast levels between the initial phase and remission phase of ALL (p<0,001). However, the multivariate logistic regression analysis yielded statistically non-significant results (p > 0.05). Conclusion: In this study, we found a significant differences of LDH and blast between the initial phase and remission phase of ALL. LDH and blast may be a promosing prognostic factor to assess ALL.